Mengoptimalkan Potensi Penyandang Disabilitas Melalui Pelatihan Seni Tari Di Sanggar Mulyo Joyo Enterprise Surabaya - mulyani, sri (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
This Community Service Program (PkM) is oriented towards increasing community awareness to optimize the potential of people with disabilities through dance training at Sanggar Mulyo Joyo Enterprise Surabaya. Disability is a condition where an individual has a physical or mental impairment that limits their ability to perform certain activities or tasks, as normally expected. Humans are expected to be perfect, capable of fulfilling their physical and psychological needs. However, in reality, some individuals experience delays in their development, known as disabilities. Through dance education for children with disabilities, this program aims to restore human function as a cultural being. This program is implemented using the Training and Capacity Building method through a Service Learning approach. The learning process and methods used in the application of body therapy through dance education at Sanggar Tari Mulyo Joyo Enterprise involve several steps, including the learning process and methods used. The participants of this program are children with various types of disabilities from Surabaya and surrounding areas (Sidoarjo and Gresik). The registration process to join the program is done without selection, usually through natural interest, where children who are interested in dance can join. The imitation method is a teaching approach where the trainer demonstrates a process of body movement being studied, accompanied by oral explanations, and then the students imitate. The results of this program conclude that the learning method used is effective in teaching dance to children with disabilities, as many of them tend to imitate, allowing them to dance according to their capacity